Faktor-Faktor yang Mempengaruhi Efisiensi Teknis pada Usahatani Padi Lahan Pasang Surut di Kecamatan Anjir Muara Kabupaten Barito Kuala Kalimantan Selatan - Ahmad Yousuf Kurniawan (AGRIDES: Jurnal Agribisnis Perdesaan, 2012)
Tidal area is one of agricultural resources which have high economic value if it is managed well. However, as marginal land, its development meets few challenges. One of them is low productivity because of input use efficiency. These research objectives are to analyze factors which influence the production of tidal rice farming, its technical efficiency level and the factors which influence this efficiency. Data from previous study were used after the data were modified based on the research objectives. The data were analized by stochastic production frontier to determine the factors and the level of technical efficiency. The result showed that seeds, fertilizers, pestisides, and labor affected rice production significantly. The level of farmer’s technical efficiency was very high, where it was not significantly influence by farmer’s age, education and dependency ratio. The study also suggested that farmer should use more organic fertilizer. The availability of skilled labor in agriculture sholud be concerned by government.